Implementation of the IMAKOM Organization Presence (Computer Student Association) Panca Budi Medan Development University Using QR Code-Based ID Cards: Implementation of the IMAKOM Organization Presence (Computer Student Association) Panca Budi Medan Development University Using QR Code-Based ID Cards - Kairul Fahmi; Sri Wahyuni; Muhammad Iqbal; Eko Hariyanto (Jurnal Mantik, 2020)
Progress in the field of information systems today has helped a lot in processing data that is very appropriate in supporting the processing of data into information. One of the technologies in question is the development of software applications, especially for mobile devices. One of the fastest mobile devices is a Smartphone. In writing this thesis, the writer raises the title of the thesis of Attendance in the Organization of IMAKOM (Computer Student Association) Medan Unpab Based on Id Card Using Qr due to the still manual validation process at imakom organization so with this application later it will attendance online and the data generated online real-time. This application is made using Android smartphone technology because of the many members of imakom using this smartphone because it has many advantages such as the availability of social media and can be used anytime and anywhere, in learning java programs that can be run on this smartphone, in this application later it will do a barcode performance in the form of QR code which will later be compiled to the database automatically and generate reports in real-time.